Strategies for Developing Teachers’ Pedagogical Competence in Implementing the Merdeka Curriculum in Grade III at SD Negeri 06 Kampung Lapai - Nurfaiza Nurfaiza; Gusnita Efrina; Ayunis Ayunis; Gingga Prananda (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
Primary education plays an important role in shaping the quality of human resources, therefore the implementation of the Merdeka Curriculum requires teachers to possess adequate pedagogical competence. This study aims to describe the pedagogical competence developed by Grade III teachers and the strategies they use in implementing the Merdeka Curriculum at SDN 06 Kampung Lapai. This research employed a qualitative method with a descriptive approach. The data sources consisted of the principal, Grade III teachers, and Grade III students. Data were collected through observation, interviews, and documentation, while data analysis was carried out through data reduction, data display, and drawing conclusions. The results of the study show that Grade III teachers already demonstrate good pedagogical competence, including the ability to understand student characteristics, design learning based on student needs, conduct lessons in a conducive way, and evaluate learning outcomes continuously. The strategies applied include collaboration among teachers in designing lesson modules, sharing experiences, and using technology as a supporting tool or medium that can enhance students’ learning experiences. This study concludes that the development of teachers’ pedagogical competence makes an important contribution to the successful implementation of the Merdeka Curriculum, particularly in creating learning that is adaptive, innovative, and relevant to students’ needs.